Adsorption of Malachite Green Using Rice Husk-Based Adsorbents - Angelie Uni Mapong Anak Manok; Farhanny Ismail; Dhia Zur’Ain Noor Salizam; Nor Atikah Husna Ahmad Nasir; Rui Hong Wu; Eric D. Van Hullebusch; Tay, Chia Chay (International Journal of Integrated Engineering, 2024)
This study investigates the adsorption of Malachite Green using rice husk-based adsorbents of chitosan alginate rice husk beads and rice husk powder. The methodology involved preparation of adsorbents and stock solution, adsorption study, evaluation of kinetic and isotherm models and characterization of adsorbent. The selected malachite green adsorption conditions were 50% removal of Malachite Green at 1.35 g for chitosan alginate rice husk beads and 0.02 g for rice husk powder, 60 minutes contact time and 5 mg/L initial Malachite Green concentration. Both adsorbents were fitted to the pseudo-second-order kinetic model rather than the pseudo-first-order kinetic model, indicating chemisorption is the rate-limiting step. For the isotherm study, chitosan alginate rice husk beads were better fitted to the heterogeneous Freundlich isotherm model, while rice husk powder matched better with the homogeneous monolayer Langmuir isotherm model. Chitosan alginate beads showed lower adsorption performance than rice husk powder due to blocked functional groups. The FTIR characterization showed functional groups -OH, -NH, -C-H and C=C present on both adsorbents. For chitosan alginate beads, the shift, disappearance and appearance of new peaks after Malachite Green adsorption indicated bonding breakdown and reaction occurred with Malachite Green, thus new bonding was formed. Scanning electron microscopy (SEM) micrographs illustrated surface morphology for both adsorbents were changed from smooth to rough surface and porous were filled by particles after Malachite Green adsorption. In this study, rice husk-based adsorbent has the potential to be used for removing Malachite Green from aqueous solutions, especially in pilot study or industrial applications.